Understanding the hydrogen effect on pop-in behavior of an equiatomic high-entropy alloy during in-situ nanoindentation. (30th January 2022) - Wang, Dong; Lu, Xu; Lin, Meichao; Wan, Di; Li, Zhiming; He, Jianying; Johnsen, Roy
Highlights: In-situ electrochemical nano-indentation test was applied on Cantor alloy. The pop-in behavior was investigated under different H charging conditions. Both pop-in width and load were reversibly reduced by H. The H reduction effect on pop-in width is more noticeable than that of pop-in load. An energy balance model was used showing H reduced dislocation mobility. Abstract: The variations in the pop-in behavior of an equiatomic CoCrFeMnNi high-entropy alloy under different hydrogen charging/discharging conditions were characterized via in-situ electrochemical nanoindentation. Results show that hydrogen accumulatively reduces both pop-in load and width, among which the reduction of pop-in width is more noticeable than that of pop-in load. Moreover, the hydrogen reduction effect on both pop-in load and width is reversible when hydrogen is degassed during anodic discharging process. Particularly, the hydrogen-reduced pop-in width was studied in detail by a comprehensive energy balance model. It is quantitatively shown that the dissolved hydrogen enhances lattice friction, leading to an increased resistance to dislocation motion. As a result, fewer dislocations can be generated with a higher hydrogen concentration, causing a smaller pop-in width. This is the first time that the pop-in width indicated dislocation mobility under hydrogen impact is quantitively revealed. Graphical abstract: Image, graphical abstract